Skrining Kemampuan Bahasa Anak Pra Sekolah : A Pilot Project - Hafidz Triantoro Aji Pratomo; Arif Siswanto; Windiarti Dwi Purnaningrum (Poltekkes Kemenkes Surakarta, 2018)
Abstract : Language, Pre School, Screening. Language skills are important for a child to be able to receive information and knowledge at school and in his home environment. This child's language skills should be an important concern of all elements involved with child education, including speech therapists in an effort to monitor the child's language development before entering school. This study aims to find out the language skills profile of pre-school children aged 4-6 years. Participants were recruited from Surakarta Kindergarten with a total of 36 children to participate in this study with an age range between 4-6 years. Screening is given to participants. It is the screening result that will reflect the receptive and expressive language profile of the child. There are six test items that can be used to screen the language skills of pre-school children:simple commands, expressive vocabulary, color names, answer questions, sentence memory, and digit memories. Internal correlation of simple command grain r = 0.791 (p = 0.000), expressive vocabulary grain r = 0.749 (p = 0.000), the item named color r = 0.739 (p = 0.000), the item answered r = 0.754 (p = 0.000) item memory sentence r = 0.879 (p = 0.000), and the item memory digit r = 0.816 (p = 0.000). The value of internal validity or correlation between items in the language development screen is good enough because all correlated items have correlations with low probability values.